2006
DOI: 10.5032/jae.2006.02093
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Experienced by New Mexico Agricultural Education Teachers in Including Special Needs Students

Abstract: Approximately 19% of the students enrolled in agricultural education in New Mexico are classified as special education students. The purpose of this descriptive-correlational study was to describe the challenges experienced by agricultural education teachers in New Mexico when including special needs students in their programs. A census of New Mexico secondary school agricultural education teachers received a mail questionnaire during spring and summer 2003. Most programs in the state offered instruction in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Success in this area will require teachers to overcome this fear through self-assurance, experience and professional development (Dormody et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Success in this area will require teachers to overcome this fear through self-assurance, experience and professional development (Dormody et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Center and Ward (1987) acknowledged that "teachers' attitudes may be significantly modified by their pre-service training and the nature of their subsequent professional experience" (p. 41). Dormody, Seevers, Andreasen, and VanLeeuwen (2006) found that agriculture teachers who had taken more formal courses on including students with disabilities felt more prepared to include students with disabilities in their classroom/laboratories.…”
Section: Statedmentioning
confidence: 99%
See 1 more Smart Citation
“…All three components have been shown to be beneficial to students with special needs. Dormody, Seevers, Andreasen, and VanLeeuwen (2006) concluded that emphasis should be placed on including students with special needs in FFA and SAE. In a study conducted by Schwager and White (1994), Oklahoma agriculture teachers determined that SAE was beneficial to students with special needs and these students should be encouraged to have an SAE program.…”
Section: Introductionmentioning
confidence: 99%
“…Reflective practice, according to Dormody, Seevers, Andreasen, and VanLeeuwen (2006), is critical for the teacher who must develop "competency in working with disabled students" (p. 94). Reflection is critical to all teachers but particularly necessary when dealing with the unfamiliar challenges faced when instructing SLD students to navigate the challenges particular to them.…”
Section: Inclusionmentioning
confidence: 99%